2013
DOI: 10.18489/sacj.v50i1.175
|View full text |Cite
|
Sign up to set email alerts
|

South African physicians’ acceptance of e-prescribing technology: an empirical test of a modified UTAUT model

Abstract: E-prescribing systems hold promise for improving the quality and efficiency of the scripting process. Yet, the use of the technology has been associated with a number of challenges. The diffusion of e-prescribing into physician practices and the consequent realisation of its potential benefits will depend on whether physicians are willing to accept and engage with the technology. This study draws on the Unified Theory of Acceptance and Use of Technology (UTAUT) and recent literature on user trust in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 53 publications
2
32
2
Order By: Relevance
“…Although, the result of Jason et al's study (19) is consistent with the results of our study, the result of this part of the study is not consistent with those of the Wills et al (15) and Holtz and Krein's studies (27). Although, most of the previous studies signify the relationship between social influences and use intention of technology, this study shows that there is no significant relationship between these two factors.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Although, the result of Jason et al's study (19) is consistent with the results of our study, the result of this part of the study is not consistent with those of the Wills et al (15) and Holtz and Krein's studies (27). Although, most of the previous studies signify the relationship between social influences and use intention of technology, this study shows that there is no significant relationship between these two factors.…”
Section: Discussioncontrasting
confidence: 84%
“…the acceptance and use of technology (17). Jason et al in a study entitled "south African physicians' acceptance of e-prescribing technology: an empirical test of a modified UTAUT model" concluded that the facilitating conditions have the most important influence on the acceptance of e-prescribing; also, the cost and the social influence had the lowest effect on the use of acceptance of e-prescribing by physicians (19). In a study entitled "Using the UTAUT Model to Explore Iranian Physicians and Nurses' Intention to Adopt Electronic Patient Records" conducted by Hamidfar et al the relationship between the parameters of UTAUT and behavioral intention was investigated among 113 physicians and nurses of Toos, Shariaty, and Dey hospitals of Tehran city by using a questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The e-prescribing system ensures the provision of enough specific and required information to fill a prescription. Warning and alert systems at the point of care may assist in averting adverse drug events.…”
Section: The Advantages and Disadvantages Of Electronic Scriptsmentioning
confidence: 99%
“…The system also improves formulary adherence to the patient's health plan or insurance, permitting substitution of less expensive drug alternatives. [7] Furthermore, automated prescription renewals may be submitted, increasing patient convenience. Clinicians using e-prescribing systems can manage their patients' medications safely and efficiently and also have the convenience of greater prescribing mobility.…”
Section: The Advantages and Disadvantages Of Electronic Scriptsmentioning
confidence: 99%
See 1 more Smart Citation